Q: Is xy and yx equivalent

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

xy = x ÷x y = 1

This gives us the equations: n = xy = yx x != y (Note that for this example, the != stands for not equal to similar to some programming languages.) xy always equals yx due to the communtative property of multiplication. So there are actually an infinite number of answers. Some are given below: 6 = (2)(3) = (3)(2), 2 != 3 12 = (3)(4) = (4)(3), 3 != 4

xy - xy = 0

If y = 0 then yx - 5 = 0*x - 5 = 0 - 5 = -5

The GCF is xy

Related questions

Yes, xy is the same as yx, but should always be written as xy.

If you have a scientific calculator, it should have a key labelled either xy, or yx. Use this for powers.If you have a scientific calculator, it should have a key labelled either xy, or yx. Use this for powers.If you have a scientific calculator, it should have a key labelled either xy, or yx. Use this for powers.If you have a scientific calculator, it should have a key labelled either xy, or yx. Use this for powers.

Ya tengo la (entrada) XY; me quedo con la (entrada) YX

xy and yx are identical so you have 2xy = 545 ie xy = 272.5. Possible answers 5 and 54.5, 10.9 and 25 etc

true

xy = x ÷x y = 1

The correct order is XY, where X represents the larger chromosome and Y represents the smaller, sex-determining chromosome.

4xy + x3y + yx2 + yx + 3yx = x3y + x2y + 8xy = (xy)(x2y + x + 8)

f'(x)xy=yx(y-1) f'(x)2=2x1=2x

don't know.want an answer

This gives us the equations: n = xy = yx x != y (Note that for this example, the != stands for not equal to similar to some programming languages.) xy always equals yx due to the communtative property of multiplication. So there are actually an infinite number of answers. Some are given below: 6 = (2)(3) = (3)(2), 2 != 3 12 = (3)(4) = (4)(3), 3 != 4

The problem to solve is: xy+x+3y+3 Multiply y and x Multiply the y and x Multiply y and x The y just gets copied along. The x just gets copied along. The answer is yx yx x*y evaluates to yx x*y+x evaluates to yx+x Multiply y and 3 Multiply y and 1 The y just gets copied along. The answer is y y 3*y evaluates to 3y The answer is yx+x+3y x*y+x+3*y evaluates to yx+x+3y The answer is yx+x+3y+3 x*y+x+3*y+3 evaluates to yx+x+3y+3 ---- The final answer isyx+x+3y+3----